Freedom of expression -The Clash of Rights - Baramuli, Andhika Yahya Santiago (Advances in Social Sciences Research Journal, 2021)
This article will examine the shift in the role of freedom of expression based on recent events, observing how the right to freedom guaranteed by law has shifted into a coercive political tool in modern democracy. The results of this article show that, freedom of expression has been melted and shaped into a shield into a sword. This has changed from what was traditionally a negative role to guarantee people's freedom from arbitrary exercise of power, to a positive role in which people can exercise their liberties against their own rights.